1873 Ky. Acts 35-36 - (:unkn) unknown (My University, 1873)
Pub. Acts ch. 767§ 1-9: If two or more persons shall unlawfully confederate or band together, and go forth armed or disguised, they shall each, on conviction thereof, be imprisoned in the penitentiary not less than six nor more than twelve months, or fined, in the discretion of the jury, in a sum not less than one hundred nor more than five hundred dollars, and imprisoned in the county jail for a period of not less than three nor more than six months.
Keywords: MILITIAS